Peran Analisis SWOT Dalam Pengembangan Produk Baru: Studi Kasus di Toko Dapur Manis - Wijaya, Thover Aldi; Irsandi, Wildan Aldi; Steven, Willy Aldi; Sanjaya, Vicky F (Lensa Ekonomi, 2024)
Sweet Kitchen Cake Shop is one of the fast-growing culinary businesses in Mesuji city. Established in 2015, this shop offers various types of traditional and modern cakes with distinctive flavors. Along with the growth of the culinary industry in the city of Mesuji, Sweet Kitchen Cake Shop faces increasingly fierce competition. To maintain and improve competitiveness, shop owners want to develop new products that can attract consumer interest. Research methods are scientific ways to obtain data with specific purposes and uses. The scientific method means that research activities are based on scientific characteristics, namely rational, empirical, and systematic (Bungin, 2003: 3) and use several methods such as 1) Types of Data and Data Sources 2) Research Variables 3) Population5) Data Collection Methods Data collection methods are techniques or ways that researchers can use to collect data. Data collection methods as a method that is independent of data analysis methods or even becomes the main tool for data analysis methods and techniques 5) Data Collection Methods 4) Sample5) Data Collection Methods Data collection methods are techniques or ways that researchers can use to collect data. Data collection method as a method that is independent of data analysis methods or even becomes the main tool for data analysis methods and techniques A. SWOT Analysis of Sweet Kitchen Cake Shop Based on the results of data collection and data analysis, a SWOT matrix for Sweet Kitchen Cake Shop is obtained as follows: Strengths Weaknesses Threats Opportunities SWOT analysis plays an important role in directing new product development strategies at Toko Kue Dapur Manis. Through the identification of strengths, weaknesses, opportunities, and threats, companies can formulate strategies that are in accordance with internal and external conditions. Strategies that can be applied include developing new products based on local raw materials, increasing marketing capabilities, product diversification, and efforts to improve operational efficiency and cost management. Implementation of the right strategy is expected to help Toko Kue Dapur Manis in increasing competitiveness and expanding the market.